Inclusion of the elements of the Clinical Caritas Veritas process in the neonatal intensive care unit (Research, Society and Development, 2024)
This study aims to promote self-reflection among the nursing team about the possibility of human care that considers the theoretical precepts of Unitary Caring Science, and to present the elements of the Clinical Caritas Veritas process, correlating them with the theoretical precepts. This is an exploratory-descriptive qualitative study. The data were collected, after favorable opinion, between February and June 2023. The participants were professionals who met the inclusion criteria: nurses or nursing technicians present in the period determined for data collection; working in the afternoon shift, regardless of the time of performance. Exclusion criteria: professionals on vacation, health/maternity leave, or absent for any other reason in the sector during the data collection period. Data analysis used Yin methodology. As a result, to facilitate understanding, three phases were classified: Pre-introduction to the elements of the Clinical Caritas Veritas Process - first non-participant observation; Integration Phase - counted with the elaboration of a welcoming space where over 30 meditation sessions were held together with conversation circles; and Post-insertion phase - return to the field for new non-participant observation. The present study strengthens the importance of a private environment that can be used as a refuge, regularly, by employees in a way to influence their personal/professional satisfaction and interpersonal relationships, with direct repercussions on the way of caring for and perceiving the other.